Nanoindentation strain-rate jump tests for determining the local strain-rate sensitivity in nanocrystalline Ni and ultrafine-grained Al - Maier, Verena; Durst, Karsten; Müller, Johannes; Backes, Björn; Höppel, Heinz Werner; Göken, Mathias (Journal of Materials Research, 2011)
A nanoindentation strain-rate jump technique has been developed for determining the local strain-rate sensitivity (SRS) of nanocrystalline and ultrafine-grained (UFG) materials. The results of the new method are compared to conventional constant strain-rate nanoindentation experiments, macroscopic compression tests, and finite element modeling (FEM) simulations. The FEM simulations showed that nanoindentation tests should yield a similar SRS as uniaxial testing and generally a good agreement is found between nanoindentation strain-rate jump experiments and compression tests. However, a higher SRS is found in constant indentation strain-rate tests, which could be caused by the long indentation times required for tests at low indentation strain rates. The nanoindentation strain-rate jump technique thus offers the possibility to use single indentations for determining the SRS at low strain rates with strongly reduced testing times. For UFG-Al, extremely fine-grained regions around a bond layer exhibit a substantial higher SRS than bulk material.
WW1::893